Patterns of Building Women between Marginalization and Personal Rebellion in Samiha Khreis’s Publications - Al-Naimat , Zain Mansour Salem; Omar Muhammad Al-Khatib, Abdullah (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to demonstrate the patterns of constructing a woman’s personality in examples of Samiha Khreis’s novels, and to clarify the image of women between rebellion and marginalization, and the impact of this on a woman’s relationship with others. Methods: The study adopted the analytical approach to Samiha Khreis’s novels within the framework of studying the patterns of constructing women’s characters in her novels between rebellion and marginalization. Results: Building a woman’s personality between rebellion and marginalization is represented by the realistic presentation of the woman’s image and conditions, her relationship with those around her, and her relationship with herself, revealing her rebellion, her struggle with others, her dreams, and her will. The woman's character is characterized by an impactful presence on the reader in light of the rebellion and marginalization to which women are exposed. Conclusion: The realistic feature imposed by the novelist Samiha Khreis on the relationship of women with others and her presence in her novels revealed the position of the female in the human conflict, in which the strength, rebellion, weakness, and marginalization of women were balanced. Women were characterized by the diversity of their roles in which they contributed to building the novelistic event in the personal style specific to women.